A Theory of Disagreement in Bargaining - Crawford, Vincent P. (Econometrica, 1982)
[This paper proposes a simple theory to explain bargaining impasses, which is based on Schelling's view of the bargaining process as a struggle between bargainers to commit themselves to favorable bargaining positions. Because bargaining impasses are generally Pareto-inefficient, anything involving a positive probability of impasse is Pareto-inefficient as well. It is demonstrated that in spite of this avoidable inefficiency, when successful commitment is uncertain and irreversible it can still be rational for individuals to attempt commitment and thereby risk an impasse; in a leading special case, the model reduces to a Prisoner's Dilemma game, in which only strategic-dominance arguments are needed to establish this conclusion. Further, making commitment more difficult, or changing the costs of disagreement in a way that makes available a wider range of settlements that are better for both bargainers than disagreement, need not always lower the probability of impasse, in spite of the conventional wisdom to the contrary.]